THE EFFECT OF PRODUCTION COST AND OPERATIONAL COSTS ON NET INCOME IN SMEs DARSA FRUIT CRIPS - Sularni, Sularni; Afif, Muhammad Faris; Yohanson, A. K.; Puspita, Indah Lia (ITB AAS Indonesia Surakarta, 2024)
Purpose: This study aims to examine the effect of production costs and operational costs partially and simultaneously on net income in SMEs. Design/methodology/approach: Production costs and operational costs as independent variables, while net income as the dependent variable. This study uses a quantitative approach. The research samples during 2018 - 2021. Data collection techniques are in the form of documentation and interviews. Data analysis used multiple linear regression, with SPSS statistics tools the t-test and f-test. Research limitations/implications: The finding reveal that partially production costs have a significant positive effect on net income, and operating costs has a significant negative effect on Net incomes. while simultaneously production cost and operational cost have a significant effect on net income. Practical implications: This study gives suggestion for SMEs should be able to manage Production Costs and control Operational Costs properly in order to generate maximum profits and avoid losses that can cause bankruptcy in SMEs businesses. Originality/value: This research gives empirical evidence the relationship production costs and operational costs on Net Income for SMEs Paper type: Research paper Keyword: Production Costs, Operating Costs, Net Income, Small Medium Enterprises